Safety and functional outcomes associated with short-term rehabilitation therapy in the post-operative management of tibial plateau leveling osteotomy - Romano, Laura S. (Can Vet J, 2015)
This retrospective cohort study using electronic questionnaires compared the perioperative complication rates of tibial plateau levelling osteotomy (TPLO) surgery and the 8-week, 6-month, and 1-year functional outcomes, between rehabilitation and traditional post-operative management. Dogs were placed into 1 of 2 cohort groups based on attending veterinarian’s selected management: i) “traditional” involving restriction to cage rest and leash walking, and ii) “rehabilitation” performed by a certified practitioner. There was no statistically significant difference in complication rates in the perioperative period between the 2 treatment cohorts (P > 0.1). The rehabilitation group was 1.9 times more likely to reach full function at 8 wk (P = 0.045). Conversely, the traditional group was 2.9 times more likely be categorized as having unacceptable function at 8 wk after surgery (P = 0.05). This study suggests that rehabilitation performed by a certified practitioner is safe and may improve short-term outcomes when used in the initial postoperative management for dogs treated with TPLO.